Ag Incorporation with Controlled Grain Growth Enables 12.5% Efficient Kesterite Solar Cell with Open Circuit Voltage Reached 64.2% Shockley–Queisser Limit. (15th April 2021) - Gong, Yuancai; Qiu, Ruichan; Niu, Chuanyou; Fu, Junjie; Jedlicka, Erin; Giridharagopal, Rajiv; Zhu, Qiang; Zhou, Yage; Yan, Weibo; Yu, Shaotang; Jiang, Jingjing; Wu, Sixin; et al.
Abstract: The large open‐circuit voltage deficit ( V oc, def ) is the key issue that limits kesterite (Cu2 ZnSn(S, Se)4, [CZTSSe]) solar cell performance. Substitution of Cu + by larger ionic Ag + ((Ag, Cu)2 ZnSn(S, Se)4, [ACZTSSe]) is one strategy to reduce Cu–Zn disorder and improve kesterite V oc . However, the so far reported ACZTSSe solar cell has not demonstrated lower V oc, def than the world record device, indicating that some intrinsic defect properties cannot be mitigated using current approaches. Here, incorporation of Ag into kesterite through a dimethyl sulfoxide (DMSO) solution that can facilitate direct phase transformation grain growth and produce a uniform and less defective kesterite absorber is reported. The same coordination chemistry of Ag + and Cu + in the DMSO solution results in the same reaction path of ACZTSSe to CZTSSe, resulting in significant suppression of CuZn defects, its defect cluster [2CuZn + SnZn ], and deep level defect CuSn . A champion device with an efficiency of 12.5% (active area efficiency 13.5% without antireflection coating) and a record low V oc, def (64.2% Shockley–Queisser limit) is achieved from ACZTSSe with 5% Ag content. Abstract : The same coordination chemistry of Ag + and Cu + in dimethyl sulfoxide solution results in the successful fabrication of solid solution (Ag x, Cu1− x )2 ZnSnS4 ( x = 0≈1). The novel Ag incorporation strategy significantly reduces band tailing, and a champion kesterite solar cell with an efficiency of 12.5% and a record low open circuit voltage ( V oc ) loss ( V oc / V oc SQ of 64.2%) is achieved with 5% Ag incorporation.